The effect of individual factors on user behaviour and the moderating role of trust: An empirical investigation of consumers' acceptance of electronic banking in the Kurdistan Region of Iraq - Yadgar Taha M. Hamakhan (Financial Innovation, 2020)
The popularity of self-service technologies, particularly in the banking industry, more precisely with electronic banking channel services, has undergone a major change as individuals' lifestyles develop. This change has affected individuals' decisions about accepting any new Information Technology, and Information Communications Technology services that are electronically mediated, for example, E-Banking channel services. This study investigates the effect of Individual Factors on User Behaviour, and the moderating role of Trust in the relationship between Individual Factors, and User Behaviour based on the Unified Theory of Acceptance and Use of Technology. This research proposes a model, with a second-order components research framework. It improves current explanations of the acceptance of electronic banking channel services. Furthermore, this study highlights the role of trust on the acceptance of electronic banking channel services, which is the most crucial consideration in customers' decisions to accept electronic banking channels services. Thus, trust is the spine of the system in the Kurdistan Region of Iraq. Data were collected using an online questionnaire that received 476 valid responses from academic staff who work at the University of Sulaimani. The model tested data using the Partial Least Squares-Structural Equation Modelling approach. The results show that Individual Factors have a positive effect on User Behaviour. Besides, results show that trust moderates the relationship between Individual Factors and User Behaviour.
Keywords: 650; Cash society; Offline banking; Technology acceptance model; Decision makers; PLSpredict